2020
DOI: 10.1007/s00464-020-07499-3
|View full text |Cite
|
Sign up to set email alerts
|

Video consultation during follow up care: effect on quality of care and patient- and provider attitude in patients with colorectal cancer

Abstract: Background Video consultation (VC) is gaining attention as a possible alternative to outpatient clinic visits. However, little is known in terms of attitude, satisfaction and quality of care using VC over a face-to-face (F2F) consultation. The aim of this observational survey study was to compare the attitude and satisfaction with VC amongst patients suffering from colorectal cancer and their treating surgeons at the outpatient surgical care clinic in a tertiary referral centre. Methods A patient-preference mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 23 publications
5
88
0
4
Order By: Relevance
“…9 Similarly, telemedicine via videoconference is equal in patient satisfaction and perceived quality of care. 4 Surprisingly in our study (mobile application and telemedicine) were not the preferred method and this is likely due to similar technology-specific reasons described by Scott Kruse et al, 19 and we need better ways to assess the quality and effectiveness of mobile health applications. 20 Linde et al examined the effectiveness of one-way text messages 7 and similar to our finding, it is not a preferred communication method.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…9 Similarly, telemedicine via videoconference is equal in patient satisfaction and perceived quality of care. 4 Surprisingly in our study (mobile application and telemedicine) were not the preferred method and this is likely due to similar technology-specific reasons described by Scott Kruse et al, 19 and we need better ways to assess the quality and effectiveness of mobile health applications. 20 Linde et al examined the effectiveness of one-way text messages 7 and similar to our finding, it is not a preferred communication method.…”
Section: Discussionmentioning
confidence: 71%
“…3 Barsom et al looked into videoconference consultation among patients with colon cancer and reported that, based on patients' preferences, videoconference is equal to face-toface consultation in terms of patient satisfaction and perceived quality of care. 4 Electronic patient portals offer the potential to enhance the patient and health care workers' communication and improve clinical care beyond the office visit. 5 When utilized effectively patient portals can empower patients to access medical records and interact with their care teams although Chan et al demonstrated low portal use in their patient populations, highlighting its infancy as a communication tool.…”
Section: Introductionmentioning
confidence: 99%
“…Videoconsultation is another method by which remote follow-up care can be delivered. It is associated with equal patient satisfaction and perceived quality of care in patients with CRC [87]. More and more biomarkers having potential diagnostic and prognostic value are identified nowadays [88].…”
Section: Discussionmentioning
confidence: 99%
“…The development of tools for video consultations or meetings should be considered as an opportunity to limit one-on-one contact [35]. If carefully employed, It will likely lead to long-term modification of our practices with a concurrent increase in patient satisfaction [36].…”
Section: Perspectivesmentioning
confidence: 99%